Imprinting and its disorders in evolutionary perspective - Tumienė, Birutė; Utkus, Algirdas; Kučinskas, Vaidutis (Acta medica Lituanica, 2014)
Bacground. Genomic imprinting is one of the best-studied epigenetic phenomena involving all the main epigenetic processes. Recent investigations led to a huge expansion of knowledge in this field and changed some established paradigms regarding imprinting establishment and maintenance. Evolutionary theories are intended to explain origins of imprinting and its evolutionary survival under the influence of selection pressure. The three main evolutionary theories based on selective asymmetry between maternally and paternally inherited alleles are kinship, sexual antagonism and maternal-offspring coadaptation theories. Though no one of them can explain all the aspects of imprinting, they are not mutually exclusive and multiple mechanisms may be at work at any given locus. Further evidences for imprinting importance come from investigations of human imprinting disorders. Eight of them have been described so far and multilocus imprinting defects have been recently discovered pointing to derangements in some common imprinting establishment / maintenance mechanisms. Conclusions. Investigations of imprinting mechanisms, evolutionary origins and derangements led to some crucial discoveries in epigenetic processes shaping both health and disease, and a huge expansion of knowledge in imprinting is anticipated in the future, especially with wider application of advanced genetic technologies.